Analisis Rasio Keuangan Pada PT. Garuda Food Periode 2019-2022 - Musyaffi, Ayatulloh Michael; Khairunnisa, Hera; Tondang, Petrus Delpansius (LPPM Universitas Negeri Jakarta, 2024)
This study analyzes PT. Garuda Food Putra Putri Jaya Tbk's financial performance from 2019 to 2022, focusing on the snack food industry. The Covid-19 pandemic significantly impacted the company in 2020, leading to decreased sales and net profit, but it recovered in 2021 with substantial growth in both metrics. Financial ratios including liquidity, solvency, profitability, and activity indicate stable liquidity and solvency but highlight a decline in return on investment (ROI) and return on equity (ROE), suggesting a need for enhanced efficiency and profitability. Short-term recommendations include improving debt management and focusing on product innovation. Medium-term strategies involve boosting operational efficiency and increasing branding efforts, while long-term plans emphasize investing in technology for production efficiency and diversifying product portfolios. These measures aim to ensure sustainable growth and strengthen the company's market position amidst evolving business challenges.